Nematode Management in Cole Crops - Z. J. Grabau; J. W. Noling (EDIS)
Many different plant-parasitic nematodes cause yield loss in cabbage, broccoli, collards, and other valuable Florida cole crops. This 13-page fact sheet written by Z. J. Grabau and J. W. Noling and published by the UF/IFAS Entomology and Nematology Department lists common symptoms, explains how to submit samples to a nematology lab such as the UF/IFAS Nematode Assay Lab for diagnosis, and describes key cultural practices to help agricultural professionals spot and manage nematode problems in cole crops.